Cardiac catheter intervention complexity and safety outcomes in adult congenital heart disease. Issue 18 (23rd March 2020) - Brida, Margarita; Diller, Gerhard Paul; Nashat, Heba; Barracano, Rosaria; Kempny, Aleksander; Uebing, Anselm; Rigby, Michael L; Gatzoulis, Michael A
Abstract : Objective: To describe the intervention spectrum, complexity, and safety outcomes of catheter-based interventions in a contemporary adult congenital heart disease (ACHD) tertiary cohort. Methods: All patients over 16 years who underwent a catheter-based intervention for ACHD in our centre between 2000 and 2016 were included. Baseline demographics, clinical characteristics, indications for and complexity of intervention, procedural complications and early and mid-term mortality were analysed. Results: Overall, 1644 catheter-based interventions were performed. Intervention complexity ranged from simple (67.5%) to intermediate (26.4%) and to high (6.1%). Commonly performed procedures were atrial septal defect (33.4%) and patent foramen ovale closure (26.1%) followed by coarctation of the aorta (11.1%) and pulmonary artery interventions (7.0%). Age at index intervention was 40±16 years, 758 (46.1%) patients were male, 73.2% in New York Heart Association (NYHA) class I, 20.2% in NYHA class II, whereas 6.6% in NYHA class III/IV. In-hospital mortality was 0.7%. Median postinterventional length of stay was 1 day. Complications occurred in 129 (7.9%) with major adverse events in 21 (1.3%). One-year postintervention survival rates were 98.7% (95% CI 98.2 to 99.2). Over the study period, there was a notable shift in intervention complexity, with a predominance of simple procedures performed in early years and more complex procedures in later years. Furthermore, the case mix during the study broadened (p<0.001) with new catheter-based interventions and a more individualised approach to therapy. Conclusion: This study shows an increasing complexity and expanding variability of ACHD catheter-based interventions, associated with low major complications, short hospital stays and low early and mid-term mortality. Ongoing investment in ACHD catheter interventions is warranted.